Caraterização metrológica de um alongâmetro - Lages Martins, L. (2016)
Submitted by Mario Pereira (majo@lnec.pt) on 2016-06-23T10:12:42Z No. of bitstreams: 1 rel 180_16 dspace.pdf: 6459841 bytes, checksum: 7896bf1045d28b1336282a4cbc158e9a (MD5)